Mfsd8 Modulates Growth and the Early Stages of Multicellular Development in Dictyostelium discoideum - Yap, Shyong Quan; Kim, William D.; Huber, Robert J. (Frontiers in Cell and Developmental Biology, 2022)
MFSD8 is a transmembrane protein that has been reported to transport chloride ions across the lysosomal membrane. Mutations in MFSD8 are associated with a subtype of Batten disease called CLN7 disease. Batten disease encompasses a family of inherited neurodegenerative lysosomal storage diseases collectively referred to as the neuronal ceroid lipofuscinoses (NCLs). Previous work identified an ortholog of human MFSD8 in the social amoeba Dictyostelium discoideum (gene: mfsd8, protein: Mfsd8), reported its localization to endocytic compartments, and demonstrated its involvement in protein secretion. In this study, we further characterized the effects of mfsd8 loss during D. discoideum growth and early stages of multicellular development. During growth, mfsd8- cells displayed increased rates of proliferation, pinocytosis, and expansion on bacterial lawns. Loss of mfsd8 also increased cell size, inhibited cytokinesis, affected the intracellular and extracellular levels of the quorum-sensing protein autocrine proliferation repressor A, and altered lysosomal enzyme activity. During the early stages of development, loss of mfsd8 delayed aggregation, which we determined was at least partly due to impaired cell-substrate adhesion, defects in protein secretion, and alterations in lysosomal enzyme activity. Overall, these results show that Mfsd8 plays an important role in modulating a variety of processes during the growth and early development of D. discoideum.